La importancia del diagnóstico del TDAH: un estudio de caso - Barrios Oneto, Giulia (2015)
This investigation reports a single case study of an 11 year-old child diagnosed by the neuropediatric involved with the case with the Attention Deficit Hyperactivity Disorder (ADHD). The objectives were to determine the diagnostic features of ADHD, identify the ADHD signs, delimit the possible disorders associated to the ADHD diagnostic, explain the consequences of the symptoms that the child could present and propose an alternative of intervention that adjusts to the child’s needs and contributes to different aspects in his life. A diagnosis is made of the child’s difficulties through a clinical interview with his parents, older sister and school teacher, also with observation instruments and psychological tests related to the surrounding problems to present an interdisciplinary approach.